Organic Mulching in Conjunction with Potassium Fertilization Effectively Regulates Soil Temperature and Enhances the Emergence, Physiological Development and Yield Performance of Late Sown Winter Maize (Zea mays L.) - Mandi, H.; Bandyopadhyay, S.; Rai, A.; Nandi, K.; Mallik, H. S.; Dutta, S.; Rai, S.; Paul, T. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during the rabi season of 2017–18 and 2018–19 to study the ‘effect of organic mulch and potassium fertilization on crop emergence, development, and productivity of maize under low temperature conditions’ at the Instructional farm of Uttar Banga Krishi Viswavidyalaya (UBKV), Pundibari, Cooch Behar, West Bengal, India. Low soil temperatures during winter significantly hinder seed germination, early crop establishment, and overall productivity of maize, while imbalanced potassium fertilization further disrupts its physiological functions. A total of 20 treatment combinations were incorporated using a split-plot design, replicated thrice. The main plots featured four organic mulches: straw mulch @10 t ha-1; weed mulch @10 t ha-1; vermicompost-mulch @ 5 t ha-1 and control, while sub-plots included six potassium levels: 0; 20; 40; 60; 80, and 100 kg ha-1. Results revealed that soil temperature, crop emergence, physiological development and productivity significantly improved with the mulching practices and potassium fertilization. Organic mulches significantly improved soil temperature and emergence rate, which varied from 11.57–15.63% at 10 DAS and 10.35–13.39% at 15 DAS over the control. Grain yield increment varieds from 23.16 to 33.17% with organic mulch compared to the control. With respect to potassium fertilization, grain and stover yields increased progressively with increasing potassium doses. Grain yield increment observed was 5.59–23.87% over the control. The highest net return and B:C were achieved under weed mulch, while potassium @ 100 kg ha-1 showed the highest values. Weed mulch combined with higher potassium fertilization would be the viable option for achieving maximum productivity and economic profitability of maize for the farming community of the Eastern Sub-Himalayan region.